LOCAL COMMUNITY’S PARTICIPATION IN DEVELOPING NUSA DUA TOURIST AREA (IN THE PERSPECTIVE OF CULTURAL STUDIES) - Madiun, I Nyoman; Ardika, I Wayan; Sirtha, I Nyoman; Suradnya, I Made (E-Journal of Cultural Studies, 2009)
That the management of various potentials has been essential in developing Balitourism has made planning one of the important elements which should be seriously andcarefully done in order to be able to control various environmental and cultural effectsresulting from the development of tourist sector. To make such a condition come true, theparticipative role of the local community as the owner of the area is very essential andcannot be bargained. In reality, however, the community’s participation cannot be easilyconducted.In this study, the theories of hegemony, deconstruction, criticism, power/knowledge, and conflict are employed. The data were obtained by observation, interview,documentation, and library research. The data were qualitatively analyzed and descriptivelypresented.The research findings show various forms of the community’s participation such asmanipulative participation, coersive participation, induced participation, and spontaneousparticipation.The factors motivating the community to participate are: the Availability ofPotential Qualified Resources, the Appearance of Tourism-Oriented New Paradigm inDevelopment among the Local Community Members, the Desire of Obtaining EconomicUsefulness, the Influence of Modernization on the Local Community Life, the Prospect ofComplementary Businesses in the Future, and the Desire of Establishing an AutonomousCommunity.The meaningfulness of the local community’s participation in developing NusaDua Tourist Area refers to the meaningfulness of Adherence to Rules, Economy, Pluralismand Multiculturalism and of Competition. There are two findings in this study; they are: (a)there is hegemony over the local community’s rights and (b) the local community is gettingmarginalized in getting access to opportunities.